Social service provision as determinant of institutional efficiency of local self-governments - Wojarska, Magdalena; Marks-Bielska, Renata; Lizińska, Wiesława; Babuchowska, Karolina (Ekonomia i Prawo. Economics and Law, 2017)
Motivation: The results presented in this paper constitute an element of the research performed as part of the project entitled ‘Institutional Efficiency vs. Local Economic Development: Modifying Factors and Interactions’. In particular, they refer to the partial objective consisting in identification and evaluation of factors that influence the institutional efficiency at the local level. Aim: The objective is to verify the hypothesis that communes manifesting greater activity in the financing of social services more frequently exceed the standard set of obligatory social services, undertake more advanced measures to improve their quality and availability and are able to accomplish the designated effects to a greater degree. Results: The hypothesis was verified on the basis of secondary data (from the Local Data Bank) and primary data (collected in the course of questionnaires circulated in the sample of 1,220 communes). Using the k-means procedure, financial activity coefficient, participation coefficient, task implementation coefficient, effect coefficient and Pearson’s coefficient, the research hypothesis was partially confirmed.